Molecular Imaging of Diabetic Foot Infections: New Tools for Old Questions - Ruiz-Bedoya, Camilo A. (Int J Mol Sci, 2019)
Diabetic foot infections (DFIs) are a common, complex, and costly medical problem with increasing prevalence. Diagnosing DFIs is a clinical challenge due to the poor specificity of the available methods to accurately determine the presence of infection in these patients. However, failure to perform an opportune diagnosis and provide optimal antibiotic therapy can lead to higher morbidity for the patient, unnecessary amputations, and increased healthcare costs. Novel developments in bacteria-specific molecular imaging can provide a non-invasive assessment of the infection site to support diagnosis, determine the extension and location of the infection, guide the selection of antibiotics, and monitor the response to treatment. This is a review of recent research in molecular imaging of infections in the context of DFI. We summarize different clinical and preclinical methods and the translational implications aimed to improve the care of patients with DFI.